Edukasi Makanan Serta Jajanan Sehat, Halal, dan Bergizi dalam Upaya Meningkatkan Kesadaran Anak Panti Asuhan - Bella Putri Khais Handrias; Andria Putri Novita Erwanda; Elita Mahda Gatra Putri; Audia Resta Wandani; Niken Hesty Wulandari (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Community service provides benefits to the community in the form of activities such as education to improve the quality of life. An orphanage is a social institution that shelters and cares for orphans. The community service carried out by UMM PMM students in group 37 batch 11 was in the form of education on healthy, halal and nutritious food and snacks for the children of the Taqwa Al-Qolbi orphanage, Malang. The participants in this service activity were residents of the Taqwa Al-Qolbi Orphanage, totaling 25 people and 6 caretakers of the orphanage. Educational activities in the form of identifying problems that often occur in the Taqwa Al-Qolbi orphanage and holding discussions with the orphanage's management to get more information about the consumption of food and snacks for the orphans. The series of stages of this service are preparation, provision of material, and implementation. Educational activities on healthy, halal and nutritious food and snacks are carried out by providing material through PowerPoint, poster and video animations to make it easier for orphanage children to understand the material and not get bored quickly, then implementing activities on the material that has been delivered in the form of giving real examples of the differences between healthy and unhealthy snacks healthy and making rice balls using halal, healthy and nutritious ingredients. The dedication activity ran smoothly and was full of enthusiasm from the orphans. Through this service program, it is hoped that the orphanage will increase the knowledge of halal, healthy and nutritious food.